Evaluation of mannan-oligosaccharides (MOS) in broiler chicken during hot humid summer using zoo technical, molecular and physio-biochemical tools - ROKADE, J J; BHANJA, S K; SHINDE, A S; SAJAD; KAPGATE, MUKESH; MANDAL, A B (The Indian Journal of Animal Sciences, 2016)
Climate resilient poultry production is a major challenge especially for hot regions like India. Accordingly, the efficacy of mannan-oligosaccharides as anti-heat stressor was studied. Broiler chicks were reared on a standard diet up to 14th day of age. Thereafter, the chicks were randomly distributed into three dietary treatment groups viz. T1 (Control group: Standard diet, T2 (Standard diet with MOS @ 0.3%) and T3 (Standard diet with MOS @ 0.5%) each with 40 birds divided in 5 replicates of 8 birds each upto 42 days of age. Experiment was carried out during hot-humid (August-September, 26.0±0.12° to 34.25±0.37°C, Rh%: 76.95±0.90 to 86.15±0.61) summer. Growth performance, immunity (4th week), physiological (4th and 6th week), biochemical (4th and 6th wk) and molecular parameters (4th and 6th wk) were recorded. Feed intake, live weight gain and FCR improved significantly (P<0.001) on MOS supplementation. The relative yield of immune organs at 4th and 6th week of age, humoral (P<0.001) as well as cellular (P<0.01) immunity also improved significantly. The percentage of haemoglobin, protein, aspartate transaminase and alanine transaminase increased significantly (P<0.001) due to MOS supplementation at 4th as well as 6th week of age. While H:L ratio, serum corticosterone and serum cholesterol decreased significantly (P<0.001) in MOS supplemented groups. Supplementation of MOS at both the levels (0.3 and 0.5%) caused significant down regulation of relative expression of HSP70 in jejunum tissues during 28th or 42nd day of age. From the results of the present study, it can be concluded that MOS supplementation @ 0.3% or 0.5% in diet of heat stressed broilers improved performance as well as welfare.